Pengaruh Lingkungan Keluarga, Pengetahuan Kewirausahaan dan Minat Berwirausaha Terhadap Perilaku Berwirausaha Siswa SMK Negeri 1 Bantaeng - Kasmawati Kasmawati; Muhammad Rakib; Rahmatullah Rahmatullah (Universitas Negeri Makassar, 2022)
The study aims to discover the influence of the family environment, entrepreneurial knowledge on entrepreneurial behavior which is mediated by the entrepreneurial interest of students majoring ini Online Business and Marketing at SMKN 1 Bantaeng. The type of this study is quantitative research with a total population of 102 students in classes XI and XII of Online Business and Marketing at SMKN 1 Bantaeng. Random sampling technique was employed and obtained 81 students as the research sample. Data were collected and processed by using path analysis tecnique. This study showed that each variable tested was valid and reliable and feasible in terms of model based on path analysis test so this study could be conducted. The results of the analysis prove that the variables of family environment, entrepreneurial knowledge, and interest in entrepreneurship have a positive and significant influence on entrepreneurial behavior and the role of interest in entrepreneurship is able to mediate the family enironment and entrepreneurial knowledge on entrepreneurial behavior. This means that the family environment variables and entrepreneurial knowledge have a positive and significant influence on entrepreneurial behavior mediated by entrepreneurial interest.